2013
DOI: 10.1136/bmj.f1811
|View full text |Cite
|
Sign up to set email alerts
|

How do we know whether medical apps work?

Abstract: Smartphone apps have the potential to transform the way the public manage their health and interact with health services, says Margaret McCartney, but regulation of medical apps has only just started

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 3 publications
(2 reference statements)
0
55
0
Order By: Relevance
“…Therefore, the literature suggests that health-care agencies should participate more to ensure patient safety and to improve the accountability and reliability of cancer-related smartphone applications [82][83][84][85][86].…”
Section: M-health Regulationmentioning
confidence: 99%
“…Therefore, the literature suggests that health-care agencies should participate more to ensure patient safety and to improve the accountability and reliability of cancer-related smartphone applications [82][83][84][85][86].…”
Section: M-health Regulationmentioning
confidence: 99%
“…For example, there were apps with instructions for using a manufacturer's AAI, apps providing text reminder services about AAI expiry dates or apps providing text alerts about allergen contamination in the food supply chain. As with other healthcare apps, there is lack of reported evaluation in the literature [42], [43]. In addition, there are no systems or apps providing feedback on injection performance or encouraging maintenance of AAI skills.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, McCartney (2013) highlights that users of health apps do not have any source of information to identify which apps provide evidence-based medical content and which do not. She reports that a study in JAMA Dermatology found that many apps designed to diagnose melanoma had a failure of 30%.…”
Section: Table 3: Recommendations To Consumers and App Developersmentioning
confidence: 99%